Penerapan Layanan Informasi Untuk Meningkatkan Minat Belajar Siswa Sekolah Menengah Atas - Djahra Fataruba (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2017)
Teaching and learning activities required stimulation. Such stimuli can be realized with the use of visuals in education. The visuals in teaching can be called information services. For that in using information services teachers should have sufficient knowledge and understanding of information services. This study aims to find and describe; (1) The use of information services in teaching and learning activities in order to increase student's interest and (2) The impact of the use of information services in Teaching and Learning Activities of Personal and Social Guidance Sessions The Importance of Managing Time at Students. This research is focused on action research in teaching and learning activities by using information service conducted on the students. The method used is unstructured in-depth interviews conducted to teachers and students, because in unstructured wawacara information will be obtained as much as possible despite the secret and sensitive nature, and allows recorded all informant affective responses that appear during the interview Take place. The results showed that the learning approach with information service (visual) in teaching and learning activities, can improve students' learning motivation in teaching and learning activities that affect the interest of students. The conclusion obtained in this study that by using media service information in teaching and learning activities, showed that the activity, motivation, and student learning achievement, has increased, so it can be confirmed that with the use of information services in Teaching and learning activities have a positive impact on student learning, because generally students prefer to see information services rather than pay attention to writing that has not been understood and understood. In the end media information services is the best solution for students in achieving learning objectives.